LECTURERS’ PERCEPTIONS ON PORTFOLIO AS AN ASSESSMENT TOOL IN ENGLISH LANGUAGE TESTING - Arifiana Tri Wulandari; Bambang Widi Pratolo; Rika Junianti (UIN Raden Mas Said Surakarta, 2019)
Assessment is an aspect of learning process which the students should have. Portfolio is a famous assessment, and it is a type of alternative assessment. The use of portfolio in English learning is expected to increase the students’ achievement. The aims of this study are (1) to understandhow the teachers give introduction of portfolio assessment toward the students, (2) to understand the system of portfolio assessment, (3) to describe the disadvantages of portfolio, (4) to identify the impacts of portfolio for the students, and (5) to understand the reasons of using portfolio in the classroom. This study was qualitative research. The participants of this study were two English lecturers who used portfolio as the assessment tool in their classes. The instrument used in this research was interview. To analyze the data, the portfolio was transcribed and analyzed manually. The result of this study showed that portfolio is very useful and effective technique to assess the students, and it can help both the lecturers and the students in learning process to get good achievement.